MINIMALLY INVASIVE TECHNOLOGIES IN THE TREATMENT OF COMPLICATED FORMS OF GALLSTONE DISEASE (International journal of medical sciences, 2026)
Objective. To evaluate the efficacy and safety of minimally invasive and hybrid surgical technologies in the treatment of complicated forms of gallstone disease.Materials and Methods. A retrospective analysis of treatment outcomes was conducted in 92 patients with complicated forms of gallstone disease treated at the Surgical Department of the Samarkand branch of the Republican Center for Emergency Medical Care from 2020 to 2025. Depending on the clinical form of the disease and the applied surgical strategy, patients were divided into groups of minimally invasive and open surgical interventions. Treatment outcomes were assessed based on the incidence of postoperative complications, mortality, and length of postoperative hospital stay.Results. Minimally invasive procedures were performed in 76 patients (82.6%), while open surgeries were carried out in 16 patients (17.4%). The most common complications were acute calculous cholecystitis (52.2%) and choledocholithiasis (29.3%). The postoperative complication rate was 8.0% in the minimally invasive group and 25.0% in the open surgery group. Postoperative mortality was 1.1% and occurred exclusively in the open surgery group. The mean postoperative hospital stay was significantly shorter in the minimally invasive group compared to the open surgery group (5.2 ± 1.6 vs. 9.8 ± 2.4 days, respectively).Conclusion. Minimally invasive and hybrid surgical technologies are effective and safe methods for treating complicated forms of gallstone disease, allowing a reduction in postoperative complications and hospital stay. A staged approach in choledocholithiasis provides optimal clinical outcomes and should be considered the preferred treatment strategy.